Chapter New reports on the presence of Callinectes sapidus (Rathbun, 1896) along the Calabrian coast - Giglio, Antonella (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This work, carried out in collaboration with professional fishing operators, aims to indicate new areas of settlement of the species Callinectes sapidus (Rathbun, 1896) present both in the Tyrrhenian Sea and in the Ionian Sea along the coast of Calabria. Part of the individuals of C. sapidus sampled were taken at the mouths of the rivers and part in the salt lakes. For each individual caught, biometrics, weight, specific areas and distribution periods were recorded